Analysis Of Internal Control System Over Merchandise Inventory At Du Anyam - Kahla, Talitha; Azizah Fauziyah; Nizza Nadya Rachmani (SEAN Institute, 2024)
Du Anyam is a social enterprise that produces and distributes woven handicrafts. From 2021 to 2023, Du Anyam consistently faced discrepancies between the actual inventory data and the records in their system which could potentially impact stock reports. This research focuses on evaluating the company’s internal control system over inventory using the COSO Internal Control Framework. The framework was selected due to its comprehensive scope. This qualitative study utilized a case study approach, collecting data through interviews, documentation, and direct observation of Du Anyam's inventory management system. The findings indicate that the internal control system over inventory at Du Anyam, based on the COSO Internal Control Framework, is less effective in three principles and ineffective in two principles. Enhancing the existing internal control system's effectiveness will necessitate several efforts, including the establishment of an audit committee, the creation of written procedures for end-to-end inventory management, and the augmentation of human resources.